Practical Analysis and Visualization Tools for Benefit-Risk Assessment in Drug Development: A Review of Recent FDA Advisory Committee Meeting Packages. (1st October 2016) - Wen, Shihua; He, Weili; Evans, Scott R.; Quartey, George; Norton, Jonathan D.; Chuang-Stein, Christy; Jiang, Qi; Ma, Haijun; Bhattacharya, Mondira
ABSTRACT: When providing advice on a medical product, a major task for FDA advisory committee members is to determine whether or not the benefits of the product under discussion outweigh its risks. Thoughtful and creative utilization of analysis methods and visualization tools often helps the sponsors and the FDA to clearly and succinctly deliver the key message, that is, whether the benefit-risk profile is favorable or unfavorable. In this article, we summarize a review of analysis methods and visual tools that were included in recent (during 2011–2014) FDA advisory committee meeting materials. We summarize the key findings related to benefit-risk (B-R) evaluations. Illustrative examples of analysis and visualization tools are provided along with potential refinements to provide readers' proper context for the appropriate use of various B-R tools in practice when evaluating the B-R balance of medical products.